Cervical Cancer in Women of Childbearing Age - Wulan, Ratih Nawang (LPPM UIN Sulthan Thaha Saifuddin Jambi, 2022)
Cervical cancer is one of the most common neoplastic diseases suffered by women in the world. The number of people with cervical cancer is nearly 500,000 new cases every year and kills 270,000 women every year. About 85% of cervical cancer events occur in developing countries, so cervical cancer is the main cancer for women in developing countries. Prevention of cervical cancer consists of primary, and secondary prevention. Primary prevention in the form of delaying the onset of sexual activity until the age of 20 years and being in monogamous contact will significantly reduce the risk of cervical cancer; the use of barier contraceptives (condoms, diaphragms, and spermicides) that play a role in protecting against viral agents.